The Writ of Amparo in the 1979 Constitution - Borea Odría, Alberto (1981)
This article discusses the evolution of the amparo in Peru since its incorporation in the 1979 Constitution, contrasting it with the habeas corpus established in the 1933 Constitution. While habeas corpus primarily protected individual liberty, amparo emerged to safeguard new social rights as well. This institution was crucial to protect a wide range of rights against violations by state authorities and private individuals. Based on this, legislation has evolved to establish clear and effective procedures, differentiating both institutions and emphasizing the need for an organic law to regulate the processes. For its part, the doctrine has played a crucial role in delineating the limits and scope of the amparo, so as to ensure its agile and fair application in cases of constitutional violation. Nevertheless, interpretative challenges persist, such as the application of amparo against unconstitutional laws and questioned judicial resolutions, which require additional clarifications in the legislation. In this context, the author concludes that the amparo represents a significant advance in the protection of fundamental rights, although its effectiveness depends on judicial interpretation and the development of complementary norms that ensure its uniform and equitable application.